How are the dynamics of village regulations related to preserving local wisdom and community culture? Consistency in laws and regulations in Indonesia - Nurfurkon, Ardika (LEGAL BRIEF, 2025)
Village regulations are often not consistent with higher laws and regulations, so some villages still face the dilemma of carrying out their role in maintaining local wisdom and community culture amidst the pressures and demands of increasingly complex times. This research aims to show the dynamics of village regulations, especially in maintaining the local wisdom and culture of village communities and their consistency in statutory regulations. This research uses a normative research method that studies relevant laws and regulations, including Law Number 6 of 2014 concerning Villages. Researchers found the strategic role of village regulations in preserving local wisdom and community culture, consistency in village regulations in statutory regulations and challenges to the existence of village regulations in supporting the preservation of local wisdom and village community culture. This is strengthened by the legitimacy regulated in Law Number 6 of 2014 concerning Villages, providing a strong legal basis for villages to regulate and carry out affairs that are beneficial to local communities.